2019
DOI: 10.1108/jed-06-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth effect of private capital inflows: a structural VAR approach for Nigeria

Abstract: Purpose The purpose of this paper is to examine the effect of shocks in the various components of private capital inflows on economic growth in Nigeria using quarterly data in the period 1986Q1–2016Q4. Design/methodology/approach The study employs the impulse response function and the forecast error variance decomposition of the structural vector autoregression (SVAR) model. Findings The research result shows that shocks in foreign direct investment (FDI) inflows and portfolio investment inflows have a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…An investigation by Anetor (2019) found that FDI accounts for significant growth in the Nigerian economy compared with other capital inflow into the economy, using data from 1961-2016, estimated by using the structural vector autoregression model (SVAR) to evaluate the effect of pricate capital inflowin the growth of Nigeria economy.…”
Section: Empirical Literature On Foreign Direct Investmentmentioning
confidence: 99%
“…An investigation by Anetor (2019) found that FDI accounts for significant growth in the Nigerian economy compared with other capital inflow into the economy, using data from 1961-2016, estimated by using the structural vector autoregression model (SVAR) to evaluate the effect of pricate capital inflowin the growth of Nigeria economy.…”
Section: Empirical Literature On Foreign Direct Investmentmentioning
confidence: 99%
“…A more recent study by (Anetor, 2019) found that FDI accounts for the significant variation in Nigeria economic growth compared to other capital inflow into the country. Using quarterly data from 1961Q1-2016Q4, estimated using the Structural Vector Autoregression model Oyegoke O.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Anyanwu (2014), the most fundamental determinant of economic growth identified by both neoclassical and endogenous growth models is investment hence a lot of empirical work focus on it. Anetor (2018), using the impulse response function (IRF) and the forecast error variance decomposition of the structural vector autoregression (SVAR) model, finds in the case of Nigeria that shocks in foreign direct investment (FDI) inflows and portfolio investment inflows have a positive and significant impact on economic growth in Nigeria. In addition, FDIs accounted for significant variation in the growth of the Nigerian economy followed by portfolio investments, while personal remittances exerted the least variation in growth.…”
Section: Literature Review 21 the Determinants Of Economic Growthmentioning
confidence: 99%